Pengaruh Pemikiran Sigmund Freud terhadap Pengembangan Konsep Bimbingan dan Konseling Islam - Manja (JURNAL ILMIAH FALSAFAH: Jurnal Kajian Filsafat, Teologi dan Humaniora, 2025)
This study aims to analyze the influence of Sigmund Freud’s thought on the development of Islamic Guidance and Counseling concepts, focusing on personality theory, counseling methodology, and their relevance to Islamic values. The research employs a qualitative approach through library research, examining primary and secondary literature related to Freud’s psychoanalytic theory and Islamic perspectives on the human psyche. The findings indicate that Freud’s thought has significantly contributed to the development of modern psychology and counseling theory, particularly in understanding the structure of personality (id, ego, superego), the unconscious mind, and internal psychological conflicts. However, from the Islamic perspective, human personality is not only determined by biological and psychological dimensions but also by spiritual elements such as ruh (spirit), qalb (heart), and nafs (self). Thus, while there are conceptual similarities between psychoanalysis and Islamic counseling in self-understanding and inner healing, fundamental differences exist in their ontological and theological foundations. The study concludes that Freud’s psychoanalytic theory can be critically adapted to the development of Islamic Guidance and Counseling as long as it remains grounded in tauhid (monotheism) and Islamic moral values derived from the Qur’an and Hadith. Integrating Western psychological theories with Islamic spirituality offers a more holistic and humanistic approach to counseling that aims for both worldly well-being and eternal happiness (sa‘ādah).